Assessment of the interrelationship between competitive confidence and cognitive skills among basketball players - Rogaleva, L.N.; Volpert, B.A.; Dosmanov, A.V.; Burkova, A.M. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the relationship between indicators of competitive confidence and mental skills among students of different levels of athletic skill. Methods and structure of the study. The study sample consisted of 25 basketball players from the first and second basketball teams of the Ural Federal University. The first team won the Belov League in the 2023-2024 and 2024-2025 seasons. To assess confidence and mental skills, the Competitive Stress Anxiety Inventory (CSAI-2), the Ottawa Mental Skills Assessment Test (OMSAT), and the Mental Toughness Scale (MTS) adapted by K.A. Bocharov et al. (2020) were used. Participation in the study was voluntary, and data was collected using the online tool Google Forms. Results and conclusions. Significant differences were found in competitive confidence scores, which were higher in the first team, which had a higher level of skill, and in cognitive anxiety scores, which were higher in the second team players. The assessment of the mental skills of athletes from the first and second teams also confirmed the existence of significant differences in terms of self-confidence, anxiety management, interference resistance, and imagination. According to the results of the correlation analysis, a relationship was found between confidence and mental toughness (rs=0.553, p<0.01), stress resistance (rs = 0.484, p<0.05), and anxiety management (rs=0.510, p<0.05). The data obtained indicate that self-confidence and mental skills of athletes are interrelated and suggest the need to develop special psychological programmes for their development.